2005
DOI: 10.1136/oem.2002.006734
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job satisfaction and health: a meta-analysis

Abstract: Background: A vast number of published studies have suggested a link between job satisfaction levels and health. The sizes of the relationships reported vary widely. Narrative overviews of this relationship have been published, but no systematic meta-analysis review has been conducted. Methods: A systematic review and meta-analysis of 485 studies with a combined sample size of 267 995 individuals was conducted, evaluating the research evidence linking self-report measures of job satisfaction to measures of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
781
4
47

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,270 publications
(891 citation statements)
references
References 23 publications
59
781
4
47
Order By: Relevance
“…Tais características incidem sobre a satisfação do servidor quanto ao seu trabalho e, consequentemente, sobre sua saúde, conforme evidenciaram Faragher et al (2005) em uma meta-análise baseada em 485 estudos, a qual apontou uma forte correlação entre os níveis de satisfação no trabalho e a saúde mental dos trabalhadores. Para os autores há evidências de que as mudanças nas condições de trabalho ocasionadas, principalmente, pelos avanços tecnológicos, possam contribuir para a diminuição dos níveis de satisfação do trabalhador (FARAGHER et al, 2005).…”
Section: Figuraunclassified
See 1 more Smart Citation
“…Tais características incidem sobre a satisfação do servidor quanto ao seu trabalho e, consequentemente, sobre sua saúde, conforme evidenciaram Faragher et al (2005) em uma meta-análise baseada em 485 estudos, a qual apontou uma forte correlação entre os níveis de satisfação no trabalho e a saúde mental dos trabalhadores. Para os autores há evidências de que as mudanças nas condições de trabalho ocasionadas, principalmente, pelos avanços tecnológicos, possam contribuir para a diminuição dos níveis de satisfação do trabalhador (FARAGHER et al, 2005).…”
Section: Figuraunclassified
“…Para os autores há evidências de que as mudanças nas condições de trabalho ocasionadas, principalmente, pelos avanços tecnológicos, possam contribuir para a diminuição dos níveis de satisfação do trabalhador (FARAGHER et al, 2005).…”
Section: Figuraunclassified
“…Perceived management commitment to safety has been linked to employee attitudes such as: job satisfaction, organisational commitment and turnover (Michael et al, 2005;Zanko and Dawson, 2012). A meta-analysis by Faragher et al (2005) found evidence that job satisfaction was associated with workers' mental health but the evidence for a link with subjective physical health was weaker.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that links job satisfaction and working conditions to mental health issues such as depression, anxiety, burn-out and self-esteem, and also physical health. 89,90 . Although these factors may affect research, they are difficult to foresee and mitigate, given the limited resources available to a research team.…”
Section: Acceptability Of the Interventionmentioning
confidence: 99%